FOXO4 Inhibits the Migration and Metastasis of Colorectal Cancer by Regulating the APC2/β-Catenin Axis - Sun, Yan; Wang, Lin; Xu, Xuehu; Han, Puqing; Wu, Jinghao; Tian, Xuan; Li, Mingsong (Frontiers in Cell and Developmental Biology, 2021)
Objective: Adenomatous polyposis coli 2 (APC2) is a colorectal cancer (CRC) tumor suppressor gene. The progression of several kinds of cancer is closely associated with Forkhead Box O4 (FOXO4). However, FOXO4’s function in CRC is unclear. This study focused on FOXO4’s role and the relationship between FOXO4 and APC2 in CRC migration and metastasis. Methods: The expressions of FOXO4, APC2, and p(S37)-β-catenin were detected in CRC tissues by immunohistochemistry, and their correlation was analyzed using the Spearman coefficient. Chromatin immunoprecipitation was used to test whether FOXO4 bind and regulate APC2 as a transcription factor. Either FOXO4 overexpression or APC2 knockdown was performed in CRC cell lines. The roles of FOXO4 and APC2 were investigated in CRC migration and metastasis. Results: FOXO4 was down-regulated in CRC tissues compared with normal, positively correlated with APC2 and p(S37)-β-catenin. FOXO4 could combine the promoter region of APC2 to up-regulate its expression and increase the phosphorylated degradation of β-catenin. Stemness genes (CD133, ABCG1, and SOX2) were inhibited by FOXO4 overexpression in SW620 and HCT116 cell lines. Overexpressed FOXO4 suppressed epithelial-mesenchymal transition and migration of CRC cell lines and metastasis of HCT116 in both the spleen and liver of the nude mice, which was reversed by APC2 knockdown. Conclusion: This research demonstrates that overexpressed FOXO4 inhibits the migration and metastasis of CRC cells by enhancing APC2/β-catenin axis, suggesting that FOXO4 is a potential therapeutic target of CRC.